ChemInform Abstract: Low‐Temperature Solution Processing of Mesoporous Metal—Sulfide Semiconductors as Light‐Harvesting Photoanodes. Issue 6 (11th February 2014) - O'Mahony, Flannan T. F.; Cappel, Ute B.; Tokmoldin, Nurlan; Lutz, Thierry; Lindblad, Rebecka; Rensmo, Haakan; Haque, Saif A.
Abstract Mesoporous films of highly crystalline Sb2S3 are prepared from a precursor paste of Sb(S2CO‐Et)3, hexylamine, and chlorobenzene by annealing at 120 °C.